2001
DOI: 10.1016/s1251-8050(01)01521-x
|View full text |Cite
|
Sign up to set email alerts
|

Les granitoı̈des de la couverture protérozoı̈que de la bordure nord du craton du Congo (Sud-Est du Cameroun et Sud-Ouest de la République centrafricaine), témoins d'une activité magmatique post-kibarienne à pré-panafricaine

Abstract: Granitoids of the Proterozoic cover of the Congo craton northern edge (South-East of Cameroon and SouthWest of the Central African Republic), witnesses of a post-Kibarian to pre-Pan-African magmatic activity. Granitoid bodies dated from the Late Mesoproterozoic intrude the Palaeoproterozoic cover of the northern edge of the Congo craton. They line up a north-south left-lateral shear zone related to the Late Kibaran tectonics. They originated from crustal melting, may be due to the thermal anomalies, that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…Early Neoproterozoic (1000 Ma) dolerites have been reported in Gabon, Congo, southern Cameroon, and Central African Republic where they cross-cut ca. 1100 Ma granites (Vicat et al, 2001); at the western edge of the Congo craton in Gabon, the onset of the break-up of the Rodinia supercontinent was associated with sedimentation, volcanism and plutonism between 1000-910 Ma (Tack et al, 2001). The Cariris Velhos orogeny (1150-950 Ma) in the Borborema Province of northeast Brazil has produced an 800 km SW-NE belt that is supposed to extend into central Africa (Van Schmus et al, 1995;Brito Neves et al, 2000, 2002.…”
Section: Significance Of Late-mesoproterozoic To Earlyneoproterozoic mentioning
confidence: 99%
“…Early Neoproterozoic (1000 Ma) dolerites have been reported in Gabon, Congo, southern Cameroon, and Central African Republic where they cross-cut ca. 1100 Ma granites (Vicat et al, 2001); at the western edge of the Congo craton in Gabon, the onset of the break-up of the Rodinia supercontinent was associated with sedimentation, volcanism and plutonism between 1000-910 Ma (Tack et al, 2001). The Cariris Velhos orogeny (1150-950 Ma) in the Borborema Province of northeast Brazil has produced an 800 km SW-NE belt that is supposed to extend into central Africa (Van Schmus et al, 1995;Brito Neves et al, 2000, 2002.…”
Section: Significance Of Late-mesoproterozoic To Earlyneoproterozoic mentioning
confidence: 99%
“…to Mesozoic Carnot basin (e.g. Yobé granite at 1160 ± 61 Ma,Vicat et al, 2001). • Dolerite dyke swarm, crosscutting Paleoproterozoic formations at the frontiers of CMR, COG and CAF.…”
mentioning
confidence: 99%
“…In the Adamawa plateau (North Cameroon), Vicat et al [9] identified previous alkaline volcanism of dolerites of Cenozoic era along the CVL. The dolerite dykes of the Adamawa plateau have chemical composition of continental tholeiites.…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
“…In Cameroon, doleritic magmatism is poorly reported. The few data available are those on dolerite dykes observed in cratonic formations of southern Cameroon [8] and in Adamawa region, North Cameroon [9], and the recent work on basaltic dyke swarms from southern part of Cameroon Volcanic Line [10]. No scientific works have been carried out on the dolerite dykes intruded into Panafrican rocks in western Cameroon.…”
Section: Introductionmentioning
confidence: 99%